A pressure, amplitude and frequency dependent hybrid damping mechanical model of flexible joint. (14th April 2020) - Hu, Jiaxin; Ren, Junxue; Zhe, Zhang; Xue, Muyao; Tong, Yue; Zou, Jie; Zheng, Qing; Tang, Haibin
Abstract: Flexible joint is the kernel part of flexible nozzle thrust vector control system. A sets of hysteresis loops of flexible joint are measured with different swing amplitudes, swing frequencies as well as vessel pressures. A hybrid damping mechanical model is adopted to predict the hysteresis loops under different operating conditions. In this model, the total restoring torque of hysteresis loop is divided into a high order polynomial elastic torque, a hybrid damping torque and an inertial torque. Herein, the damping torque can adopt to different operating conditions and the asymmetry of hysteresis loop is also considered in the modeling, which guarantees the generalization performance of the model. Moreover, there are only 4 coefficients need to be identified in each part of hysteresis loop, which has a smaller fitting error. Therefore, this model makes a good balance between generalization performance and fitting errors. It can be observed that the simulation results of this model are well consistent with the experiment results with the relative errors range from 3.01% to 8.12%. Moreover, this model is compared with linear viscous damping model as well as semi-constitutive mechanical model, and it can be seen that the model adopted in this paper are in better agreement with experiment results. Furthermore, by adopting the hybrid damping mechanical model, the servo mechanism – flexible nozzle system can also achieve a better position accuracy compared with that of linear viscous damping model with a priority up to 0.15°, since the former one has a more accurate hysteresis loop. Highlights: The model constructed in this paper can adopt to different operating conditions. The simulation results of model are well consistent with the experiment results. This model makes a balance between generalization performance and fitting errors. This model has a higher prediction precision compared with other two classic models. Based on this model, the flexible nozzle can achieve a better position accuracy.